West Nile and St. Louis encephalitis viral genetic determinants of avian host competence. - Payal D Maharaj; Angela M Bosco-Lauth; Stanley A Langevin; Michael Anishchenko; Richard A Bowen; William K Reisen; Aaron C Brault (Public Library of Science (PLoS), 2018)
West Nile virus (WNV) and St. Louis encephalitis (SLEV) virus are enzootically maintained in North America in cycles involving the same mosquito vectors and similar avian hosts. However, these viruses exhibit dissimilar viremia and virulence phenotypes in birds: WNV is associated with high magnitude viremias that can result in mortality in certain species such as American crows (AMCRs, Corvus brachyrhynchos) whereas SLEV infection yields lower viremias that have not been associated with avian mortality. Cross-neutralization of these viruses in avian sera has been proposed to explain the reduced circulation of SLEV since the introduction of WNV in North America; however, in 2015, both viruses were the etiologic agents of concurrent human encephalitis outbreaks in Arizona, indicating the need to re-evaluate host factors and cross-neutralization responses as factors potentially affecting viral co-circulation. Reciprocal chimeric WNV and SLEV viruses were constructed by interchanging the pre-membrane (prM)-envelope (E) genes, and viruses subsequently generated were utilized herein for the inoculation of three different avian species: house sparrows (HOSPs; Passer domesticus), house finches (Haemorhous mexicanus) and AMCRs. Cross-protective immunity between parental and chimeric viruses were also assessed in HOSPs. Results indicated that the prM-E genes did not modulate avian replication or virulence differences between WNV and SLEV in any of the three avian species. However, WNV-prME proteins did dictate cross-protective immunity between these antigenically heterologous viruses. Our data provides further evidence of the important role that the WNV / SLEV viral non-structural genetic elements play in viral replication, avian host competence and virulence.